Branching Processes in Biology - Kimmel, Marek (Springer, 2015)
The theory of branching processes is an area of mathematics that describes situations in which an entity exists for a time and then may be replaced by one, two or more entities of a similar or different type. It is a well developed and active area of research with theoretical interests and practical applications....